Clinical correlates and metabolic indicators of elevated fasting glucose in overweight/obese Chinese Han patients with first-episode and drug-naive major depressive disorder - Gao, Wenqi; Deng, Zhifang; Cai, Xiaonan; Zhang, Dan; Xiao, Han; Zhang, Xiangyang (Frontiers in Endocrinology, 2023)
Background: Overweight/obese major depressive disorder (MDD) patients have a high probability of developing glucose metabolism disorders; however, the results are inconsistent due to the confounding variables involved in the studies. The purpose of this study was to explore the prevalence and risk factors for elevated fasting glucose in Chinese Han patients with overweight/obese first-episode and drug naïve (FEDN) MDD. Methods: The study used a cross-sectional design and recruited 1718 FEDN MDD patients between the ages of 18 and 60 years. Socio-demographic information, anthropometric data, and biochemical parameters were collected. The 17-item Hamilton Assessment Scale for Depression (HAMD), the 14-item Hamilton Anxiety Scale (HAMA), and the Positive and Negative Syndrome Scale (PANSS) positive subscale were used to assess symptoms of all patients. Results: MDD patients with elevated fasting glucose had higher TSH, TPOAb, TC, TG, LDL-C, systolic and diastolic blood pressure levels than those with normal fasting glucose. Logistic regression analysis showed that age, TSH, TgAb, TPOA, and TG were risk factors for elevated fasting glucose, while TSH and combination all these five parameters had the potential to differentiate between patients with elevated fasting glucose and those with normal fasting glucose. Multifactorial regression analysis showed that TSH, TG, and LDL-C were independently associated with elevated fasting glucose. Conclusion: Our findings suggest a high prevalence of elevated fasting glucose in overweight/obese FEDN MDD patients. Several clinically relevant factors and metabolic parameters have an impact on elevated fasting glucose in overweight/obese FEDN MDD patients.